Proceso atención de enfermería en paciente de 53 años de edad con úlcera varicosa en miembro. - Mora Torres, Tairy Nohelia (2021)
The present clinical case is about a 53-year-old female patient who attended the consultation of the general practitioner of the General Hospital IESS Babahoyo due to pain caused by a varicose ulcer in the lower left limb, with exudate without a bad smell, and due to Complications are indicated to the patient who deserves immediate hospitalization, with which the patient refuses it. In laboratory tests it was observed that the values were normal, and Venous Doppler Ultrasound revealed venous insufficiency in the left lower limb. And with this result, the cephalocaudal assessment was carried out according to the functional patterns of Marjory Gordon and together with the physical examination, the nursing process was determined with the purpose of recovering the health of the adult and improving her quality of life.